Towards operationalization of climate-smart agriculture institutional innovations in West and Central Africa - Kpadonou, Gbedehoue Esaie; Ganyo, Kyky Desiré; Segnon, Alcade C.; Ngaido, Amadou; Diallo, Yacouba; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Accelerating the scaling of climate-smart agriculture (CSA) requires institutional innovations and interactions among stakeholders operating across scales. The West Africa CSA Alliance (WACSA) and the Central Africa CSA Alliance (CACSA) are two CSA institutional innovations operating at regional scale and aimed at facilitating dialogue and discussions among stakeholders, as well as fostering collective actions to transform and reorient agricultural systems in face of climate change. Through CAADP-XP4 and AICCRA programs, the West and Central African Council for Agricultural Research and Development (CORAF) has initiated actions aimed at reinvigorating these CSA alliances through the co-construction of sound regional programs. To this end, a mapping of sources and mechanisms of funding of climate actions and initiatives in West and Central Africa was conducted. A total of about 80 relevant funding sources and mechanisms were identified for WACSA, while for CACSA, about 59 relevant sources and mechanisms of funding were identified. These funding sources and mechanisms are to be leverages to mobilize resources to reinvigorate the WACSA and fully operationalize the CACSA to benefit the two regions. Next to this stocktaking exercises is the formulation and development of the regional CSA program concept notes. Through this co-construction process, the strategic components of the regional programs have been identified. The strong commitment of regional and national institutions to support the operationalization of the alliances and the participatory approach used for the co-construction of the alliances are key leverage points to keep up the momentum on the CSA alliances in the two regions